Ringed Seals and Sea Ice in Canada’s Western Arctic: Harvest-Based Monitoring 1992–2011 - Harwood, Lois A.; Smith, Thomas G.; Melling, Humfrey; Alikamik, John; Kingsley, Michael C.S. (ARCTIC, 2012)
We examined the relationship between ringed seal body condition and reproduction and spring sea ice conditions in prime ringed seal habitat in Canada’s western Arctic during 1992 – 2011. Since 1970, ice conditions in east Amundsen Gulf and west Prince Albert Sound have shown only a slight trend toward earlier ice clearance (breakup) in spring (3 – 7 days per decade) (p < 0.10) and no trend toward later freeze-up or increased variability in timing of spring ice clearance. A subsistence harvest – based sample of 2281 ringed seals was obtained during 1992 – 2011 from Masoyak, a traditional hunting camp located on the northwest shore of west Prince Albert Sound and less than 5 km from east Amundsen Gulf. The results revealed a statistically significant trend of decreasing mean annual body condition of ringed seals (using an index of length-mass-blubber depth [LMD]: adults, 0.14 m1.5/kg0.5/y; subadults, 0.24 m1.5/kg0.5/y) over the past two decades. A parallel result was that mean annual body condition of adults and subadults was correlated with the timing of fast ice clearance in spring (later ice clearance = worse condition). This correlation was most obvious in the extreme ice years in all sex/age groupings and was statistically significant for subadults. In mature females sampled since 1992, annual ovulation rates averaged 92.4 ± 16.3% (SD) and were greater than 80%, and mostly at 100%, in all years but two. Failure to ovulate was obvious in 2005, the most extreme late ice clearance year in our series, when only 30.0% of the mature adult females sampled ovulated. At the same time, values for seal body condition indices (adult females, LMD = 11.3; adult males, LMD = 12.4) and percent pups in the harvest (3.3%) were among the lowest recorded, and spring ice clearance was 38 d later than the 1992 – 2011 average. While this and previous studies indicate that the seal population in this core habitat has recovered from natural and extreme-year sea ice fluctuations over the past four decades, the potentially magnified ...